Transgenders: an insight to early progression - Alam, Mohammad Khursheed; Arshad, Anas Imran (International Journal of Human and Health Sciences (IJHHS), 2020)
Lack of local and national transgender-led organisations necessitates an informatory response of researchers striving to develop standards of medical and dental care for transgender communities of developing countries. Here in the Universiti Sains Malaysia in Kelantan, Malaysia, we have made efforts to conduct research and develop a better understanding of health care needs for local Bangladeshi transgender community. Currently, we are outreaching transgender community leaders for data collection with prior permissions to facilitate at least palliative treatment provision. We aim to assess the differences in dental and craniofacial morphometry of transgenders. We also focus on identifying the associations of Body Mass Index (BMI) and ABO Blood grouping with the craniofacial morphometrics. So for our knowledge goes, there is no existing database for the dental and craniofacial morphometric norms of transgenders. Our study outcomes will primarily serve orthodontists, maxillofacial surgeons and on a larger scale will facilitate forensic specialists, radiologists and other health care personnel to better understand the inherent differences and plan the desired treatments according to their specific norms. This will also encourage and empower transgenders to seek health advices and enjoy a healthy social life. The fears of violence and discrimination that transgenders face in our society have suppressed their basic health care needs for long. We need to work in globalised collaboration to address the complex array of challenges that the transgender community faces. Gender equity and indiscrimination is their birth right and we hold this responsibility to defend and fight for their rights to ensure their prosperous future. International Journal of Human and Health Sciences Vol. 04 No. 03 July’20 Page : 155